Methyl Acetate as a Co-Solvent in NMC532/Graphite Cells. Issue 5 (1st January 2018) - Li, Jing; Li, Hongyang; Ma, Xiaowei; Stone, Will; Glazier, Stephen; Logan, Eric; Tonita, Erin Marie; Gering, Kevin L.; Dahn, J. R.
Abstract : One goal of researchers focusing on lithium-ion batteries for electric vehicles is to decrease the time required for charging. This can be done by several methods, including increasing the electrolyte transport properties. Methyl acetate, used as a co-solvent in the electrolyte, has been shown by a number of researchers to increase cell rate capability dramatically but careful considerations of the impact of methyl acetate on cell lifetime have not been published to our knowledge. The impacts of methyl acetate as a co-solvent in NMC532/ graphite cells were systematically studied in this work. Ex-situ gas evolution measurements, electrochemical impedance spectroscopy, high rate charging tests, ultra-high precision coulometry, isothermal microcalorimetry and long term cycling at both 20 and 40°C were used to probe the impacts of including methyl acetate as a co-solvent. This work will be of great interest to Li-ion battery scientists developing cells that can support rapid charge and still maintain long lifetime.